2017
DOI: 10.1504/ijsmile.2017.086094
|View full text |Cite
|
Sign up to set email alerts
|

Social media adoption in higher education: a case study involving IT/IS students

Abstract: Social media adoption in higher education 63 activities based on social media, followed by the role of social influence. Based on the analysis, guidelines for planning social-media-based learning activities are proposed. Indications of further work complete the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This study is an empirical approach based on the authors' personal experiences of education and a synopsis of their previous publications related to education, teaching and learning [8,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Research Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is an empirical approach based on the authors' personal experiences of education and a synopsis of their previous publications related to education, teaching and learning [8,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30].…”
Section: Research Approachmentioning
confidence: 99%
“…The developments in ICTs, however, demand re-thinking of pedagogic principles and frameworks. The phenomenon of technology based distance mode learning [13] in the form of e-learning, mobile learning (mlearning), social media learning [8,19,21], and Massive Online Open Courses (MOOCsan online course aimed at unlimited participation, self regulated open access via the web) [28,29] in education has led to a trend towards greater openness, particularly in higher education [2]. A trend in today's learning environments are on creating, fostering, delivering and enabling learning at own place, own pace and own time with increased peer-based learning tasks and promotion of learning within Communities of Practice (COPs) [13,14].…”
Section: Research Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrigan and Choudhury (2012) propose that the outcome from Social CRM implementation along with the customer engagement model and the technologies in social media leads to increased trust, brand loyalty, co-creation and empowerment. In a study by Siakas et al (2017) in students' perception of using social media in education it was found that other factors important for social media adoption were infrastructure for using social media, social influence and experience of using social media were important factors for…”
Section: Social Crmmentioning
confidence: 99%